On the growth (rate) effects of migration - Uwe Walz (Eberhard Karls Universität Tübingen, Wirtschaftswissenschaftliche Fakultät, 1993)
Problems related to labor migration on a large scale in South-North as well as in East-West direction are high on the agenda. This papers presents an endogenous growth model for two regions with human capital formation as the engine of growth. The model is used to analyze the growth (rate) effects of migration in the host as well as in the source country. Thereby, two types of migrating individuals which differ in their ability in the human capital formation process are distinguished and the long-run effects of their respective migrations assessed. It can be shown that under certain circumstances migration increases the rate of growth in both regions. Furthermore, it will be argued that the mobility of only one type of individuals tends to equalize interregional factor rewards not only for skilled but for unskilled labour as well.
Keywords: 330; Regionales Wachstum; Arbeitsmigranten; Humankapital; Theorie